Cyp1 Inhibition Prevents Doxorubicin‐Induced Cardiomyopathy in a Zebrafish Heart‐Failure Model. (6th March 2020) - Lam, Pui‐Ying; Kutchukian, Peter; Anand, Rajan; Imbriglio, Jason; Andrews, Christine; Padilla, Hugo; Vohra, Anita; Lane, Sarah; Parker, Dann L.; Cornella Taracido, Ivan; Johns, Douglas G.; Beerens, Manu; et al.
Abstract: Doxorubicin is a highly effective chemotherapy agent used to treat many common malignancies. However, its use is limited by cardiotoxicity, and cumulative doses exponentially increase the risk of heart failure. To identify novel heart failure treatment targets, a zebrafish model of doxorubicin‐induced cardiomyopathy was previously established for small‐molecule screening. Using this model, several small molecules that prevent doxorubicin‐induced cardiotoxicity both in zebrafish and in mouse models have previously been identified. In this study, exploration of doxorubicin cardiotoxicity is expanded by screening 2271 small molecules from a proprietary, target‐annotated tool compound collection. It is found that 120 small molecules can prevent doxorubicin‐induced cardiotoxicity, including 7 highly effective compounds. Of these, all seven exhibited inhibitory activity towards cytochrome P450 family 1 (CYP1). These results are consistent with previous findings, in which visnagin, a CYP1 inhibitor, also prevents doxorubicin‐induced cardiotoxicity. Importantly, genetic mutation of cyp1a protected zebrafish against doxorubicin‐induced cardiotoxicity phenotypes. Together, these results provide strong evidence that CYP1 is an important contributor to doxorubicin‐induced cardiotoxicity and highlight the CYP1 pathway as a candidate therapeutic target for clinical cardioprotection. Abstract : Don't lose heart : Doxorubicin is a potent chemotherapy agent, but its use is limited by cardiotoxic side effects. By using a zebrafish model of doxorubicin‐induced cardiomyopathy for small‐molecule screening, cytochrome P450 family 1 (CYP1) is identified as a candidate therapeutic target for clinical cardioprotection (see figure).